2018
DOI: 10.1186/s12864-017-4409-8
|View full text |Cite
|
Sign up to set email alerts
|

A-to-I RNA editing in the rat brain is age-dependent, region-specific and sensitive to environmental stress across generations

Abstract: BackgroundAdenosine-to-inosine (A-to-I) RNA editing is an epigenetic modification catalyzed by adenosine deaminases acting on RNA (ADARs), and is especially prevalent in the brain. We used the highly accurate microfluidics-based multiplex PCR sequencing (mmPCR-seq) technique to assess the effects of development and environmental stress on A-to-I editing at 146 pre-selected, conserved sites in the rat prefrontal cortex and amygdala. Furthermore, we asked whether changes in editing can be observed in offspring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 111 publications
13
47
0
Order By: Relevance
“…The number of animals per group appears in the figures. Rats were handled in accordance with the NIH guidelines for the Care and Use of Laboratory Animals, 8th edition [ 38 ] and were bred and treated simultaneously to rats described in [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of animals per group appears in the figures. Rats were handled in accordance with the NIH guidelines for the Care and Use of Laboratory Animals, 8th edition [ 38 ] and were bred and treated simultaneously to rats described in [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using a highly accurate high-throughput targeted approach (microfluidics-based multiplex PCR and deep sequencing—mmPCR-seq [ 26 ]), we recently showed that exposing adolescent female rats to chronic unpredictable stress prior to reproduction (prereproductive stress; PRS) affects A-to-I editing in the prefrontal cortex (PFC) and amygdala of their newborn offspring. In particular, editing at the Htr2c was affected, resulting in a different pattern of Htr2c isoforms in offspring of stress-exposed versus naïve females [ 22 ]. We have previously shown that exposure of adolescent females to PRS also results in changes in behavior, stress-related plasma hormone levels, cortical gene expression and neuronal morphology in first- and second-generation offspring [ 27–31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alterations in editing might occur trans-generationally. It was reported that chronic unpredictable stress in pre-reproductive female rats affected the 5-HT 2C R RNA editing in two generations of offspring (Zaidan et al, 2018). Maternal treatment with a serotonin-specific reuptake inhibitor (SSRI), fluoxetine, after stress reversed the effect of these editing changes in the prefrontal cortex and amygdala of new born offspring (Zaidan and Gaisler-Salomon, 2015).…”
Section: Rna Editing Of 5-ht 2c R Mrnamentioning
confidence: 99%
“…Parkinson's disease is a neurodegenetative disorder affecting 2-3% of people over 65 years of age [12]. However the functional relevance of miRNA editing in PD is largely unknown, although A-to-I editing is prevalent in brain [13][14][15][16] and the editing level is gradually increasing in the developmental procedure [5,16].To comprehensively characterize miRNA editing sites in brain tissues of PD, we analyzing 43 and 88 small RNA sequencing profiles of PD and control brain tissues, respectively. We identified 421 miRNA editing sites that have significantly different editing levels in prefrontal cortices of PD patients (PD-PC) compared with control group.…”
mentioning
confidence: 99%
“…. However the functional relevance of miRNA editing in PD is largely unknown, although A-to-I editing is prevalent in brain [13][14][15][16] and the editing level is gradually increasing in the developmental procedure [5,16].…”
mentioning
confidence: 99%